Neutrophil, TLR2, and TLR4 expression in newborns at risk of sepsis - Ari Yunanto; Agustina Tri Endharti; Aris Widodo (Paediatrica Indonesiana, 2013)
Background There is increasing evidence that toll-like receptors (TLR) play a key role in the mediation of systemic responses to invading pathogens during sepsis. Saliva is an important body fluid for detecting physiological and pathological conditions of the human body. Neutrophils are participants in the acute response against pathogens in many tissues, and their influx into the oral cavity may occur at any time.Objective To compare mean neutrophils and the expression of TLR2 and TLR4 in saliva and blood of newborns at risk for sepsis to those of healthy newborns.Methods This cross-sectional study was conducted from July to December 2011 in the Division of Neonatology, Department of Child Health, Ulin General Hospital, Lambung Mangkurat University Medical School, Banjarmasin. Case subjects were newborns with sepsis risk factors (30 infants), while 30 healthy infants were in the control group. Saliva and blood specimen examinations were performed in the Biomedical Laboratory of Brawijaya University Medical School, Malang. We used T-test for statistical analyses.Results From saliva specimens, mean neutrophils were significantly higher in the case group than in the control group [14.43 (SD 12.21) % vs. 5.63 (SD 6.78) %, respectively, (P=0.021)]. In addition, mean TLR2 and mean TLR4 saliva levels were significantly higher in the case group than in the control group [TLR2: 64.97 (SD 26.42) % vs. 40.06 (SD 6.23) %, respectively, (P=0.011); TLR4: 1.5 (SD 1.61) % vs. 0.57 (SD 0.53) %, respectively, (P=0.044)]. From blood specimens, mean neutrophils were also significantly higher in the case group than in the control group [1.09 (SD 0.61)% vs. 0.21 (SD 0.09)%, respectively, (P=0.000)]. Similarly, mean blood TLR2 and TLR4 levels were significantly higher in the case group than in the control group [TLR2: 92.51 (SD 5.51) % vs. 81.74 (SD 11.79) %, respectively, (P=0.003); TLR4: 0.71 (SD 1.42) % vs. 0.12 (SD 0.06) %, respectively, (P=0.000)].Conclusion There are significant increases in neutrophils, asÂ well as neutrophil expression of TLR2 and TLR4 in the saliva and blood from newborns with sepsis risk factors compared to those of healthy newborns. [Paediatr Indones. 2013;53:132-7.]